2017
DOI: 10.4236/ojacct.2017.64009
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Banks’ Profitability: Panel Data from Qatar

Abstract: Purpose: The aim of this paper is to investigate the main determinants of banks' profitability and answer the question "what is the effect of liquidity and risk variables on the explained variation of banks' performance in Qatar?" Design/methodology/approach: A sample of six major lender banks for the period 2008-2015 is retrieved from the worldwide bankscope database. The dependent variable "Return on Average Assets (ROAA)" is taken as a function of independent variables that are basically liquidity and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…The negative influence indicates that poor economic and financial conditions increase loans default leading to lower profitability. These results are in line with Sufian (2009), Hasan and İbrahim (2014) and El-Kassem (2017). In the same vein, operation efficiency correlated negatively and significantly (1%) with profitability indicating that banks in Iran and Sudan operate at higher cost and the results of this paper reinforced Elgadi (2016), Siddique et al (2016), Obeidat et al (2013) and Wasiuzzaman and Tarmizi (2010) conclusion.…”
Section: Resultssupporting
confidence: 87%
“…The negative influence indicates that poor economic and financial conditions increase loans default leading to lower profitability. These results are in line with Sufian (2009), Hasan and İbrahim (2014) and El-Kassem (2017). In the same vein, operation efficiency correlated negatively and significantly (1%) with profitability indicating that banks in Iran and Sudan operate at higher cost and the results of this paper reinforced Elgadi (2016), Siddique et al (2016), Obeidat et al (2013) and Wasiuzzaman and Tarmizi (2010) conclusion.…”
Section: Resultssupporting
confidence: 87%
“…According to Abdulkabir et al ( 2020 ), the capital structure and operational costs were negatively correlated. El-Kassem ( 2017 ) discovered that while variance with an independent variable “Cost to Income Ratio” has a negative and significant impact on the variation in bank performance, variability in the exogenous variable such as “Total Capital Ratio” has a positive and significant impact on a bank's performance. According to Koroleva et al ( 2021 ), size, credit quality, as well as liquidity are internal factors that have a significant positive impact on banks' profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the study of the EU banking sector by Staikouras and Wood (2004) and the study of the U.S. banks by Wang and Wang (2015) found that the higher the loan‐to‐asset ratio, the lower the profitability of banks. In the same line, El‐Kassem (2017) found that the higher this ratio, the lower the profitability of banks in Qatar. Moreover, as for credit risk, contrary to the expected results, Akwaa‐Sekyi and Moreno Gené (2016) reveal a negative relationship between these two.…”
Section: Literature Review and Variablesmentioning
confidence: 83%